A social environmental model of socio-technical performance. (1st January 2012) - Whitworth, Brian; Sylla, Cheickna
This paper analyses the nature of social performance, to explain how socio-technical systems (STSs) like chat, e-markets, social networks and wikis can succeed despite being free of charge. It defines the non-zero-sum synergy gains of cooperation and how self-interested acts can collapse the society that creates them. It explains how physical human society dealt with this 'social dilemma' then relates that to the socio-technical advance. In this model, society is a social environment within a world environment, so its citizens face the dual requirements of self-interest and social-interest, which can be satisfied by anchoring one demand then managing the other, e.g., competing within a social context, as in markets, or community service within an individual context of sufficiency. Overall, the paper proposes a new social form that socio-technical systems illustrate and which could be the future of humanity.